Trends and periodicities in Krishna Basin rainfall/extremes found via hierarchical analysis - Gaurav Pakhale; Rakesh Khosa; A.K. Gosain (HydroResearch)
Analysing the spatiotemporal changes in long-term rainfall and extreme events at a river basin scale is crucial for optimal water resource management. This study examines trends in long-term rainfall and extreme event indices in the Krishna River Basin (KRB) using Indian Meteorological Department (IMD) 0.25° resolution daily precipitation data from 1951 to 2019. Methods include the Mann–Kendall trend test, Innovative Trend Analysis (ITA), Hurst's Rescaled Range (He) Analysis, and Wavelets.The results show variations in rainfall and extreme event patterns across KRB subsystems. Overall, Annual Rainfall (AR) is decreasing, with significant trends in Ghatprabha (K3), Lower Bhima (K6), and Vedavati (K9). Seasonal and monthly rainfall trends are not significant. Extreme event indices (Daily rainfall greater than 10 mm [R10], Daily rainfall greater than 20 mm [R20], and Daily rainfall greater than 40 mm [R40], the annual maximum for 1 to 7 days and starting days of such events showed the non-significant trend in some of the subsystems when analysed with statistical methods; however, graphical analysis using ITA indicates clear trends. He construed a sustainable decreasing trend and predicted a future rainfall reduction. The wavelet power spectra for different indices infer periods between 2 and 16, predominantly concentrated around 2–4 year bands. Decreasing annual rainfall in most headwater catchments, captured by most methods, suggests that KRB will experience less rainfall and fewer rainy days in the future.By discerning long-term rainfall trends and periodic patterns in the KRB, future water availability can be predicted, and extreme events can be better analysed. This analysis will be the basis for devising robust flood control measures, mitigating flood risks, and optimizing water resource allocation across sectors, thereby enhancing resilience to climate variability in future.